Outcome of pregnancy in obese and immigrant women - Mohamed, Farhia (fi=Turun yliopisto|en=University of Turku|, 2017)
The prevalence of adulthood obesity including women of reproductive age has increased at an alarming rate. Maternal obesity represents one of the most common problems in obstetric care. In Finland, the proportion of births in immigrant women have increased. These women constitute a unique challenge due to the impact culture and life experiences have in participating in maternal care. The main objective of this study was to investigate the pregnancy outcome of obese and immigrant women by conducting a PubMed search of published reviews, metaanalyses, and original studies, and published reports from other sources. The main interest was to determine the risks related to obese and immigrant pregnancy compared with normal weight and non-immigrant women, and to explore health outcomes for the mother and the offspring. The study shows that maternal obesity associates with an elevated risk of gestational diabetes, pre-eclampsia, caesarean sections (CS), thromboembolism, and post-surgical problems. The fetus has an increased risk of stillbirth, macrosomia, delivery complications, admission to neonatal intensive care unit, and later in life higher risk of metabolic syndrome, type 2 diabetes, and cardiovascular disease. Compared to native Finnish women, non-western immigrant women have a higher risk of preterm delivery, low birth weight infant, perinatal mortality, and CS. Many Somali and Kurdish women have undergone female genital mutilation associating with immediate and long-term health problems. Pregnant obese and immigrant women constitute a vulnerable group indicating that elaborate strategies to improve health and pregnancy outcome among these women are needed.